Human Security Threat Analysis in the Cambridge Analytica Case Based on the UNDP 1994 Framework - Muhamad Umar Nugroho; Vina Selvia; Ardhian Dwi Saputra (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
The rapid growth of digital technologies and social media platforms has created new challenges related to privacy, data protection, and information manipulation. One of the most prominent examples is the Cambridge Analytica scandal, in which personal data from millions of Facebook users were collected and utilized for psychographic profiling and political micro-targeting. This study aims to analyze the Cambridge Analytica case using the Human Security framework introduced by the United Nations Development Programme (UNDP) in the Human Development Report 1994. A qualitative case study approach was employed, utilizing literature review and document analysis from academic publications, official reports, investigative journalism, and policy documents related to Human Security, digital manipulation, and data exploitation. The findings indicate that the Cambridge Analytica scandal represents a contemporary Human Security threat in the digital era. The case primarily affected three dimensions of Human Security: political security, personal security, and community security. Political security was threatened through voter manipulation and interference in democratic processes; personal security was compromised through privacy violations and unauthorized data exploitation; while community security was weakened through the creation of echo chambers and increasing social polarization. The study also highlights that human vulnerabilities, including limited digital literacy, excessive trust in digital platforms, and susceptibility to psychological manipulation, played a significant role in enabling data exploitation. The findings suggest that strengthening digital literacy, improving data protection regulations, enhancing platform accountability, and promoting ethical digital governance are essential for safeguarding Human Security in the contemporary digital environment.